Parthenolide and arsenic trioxide co-trigger autophagy-accompanied apoptosis in hepatocellular carcinoma cells - Yi, Juan; Gong, Xia; Yin, Xiao-Yang; Wang, Li; Hou, Jin-Xia; Chen, Jing; Xie, Bei; Chen, Gang; Wang, Li-Na; Wang, Xiao-Yuan; Wang, Da-Chun; Wei, Hu-Lai (Frontiers in Oncology, 2022)
Although arsenic trioxide (ATO) shows a strong anti-tumor effect in the treatment of acute promyelocytic leukemia, it does not benefit patients with hepatocellular carcinoma (HCC). Thus, combination therapy is proposed to enhance the efficacy of ATO. Parthenolide (PTL), a natural compound, selectively eradicates cancer cells and cancer stem cells with no toxicity to normal cells. In this study, we chose PTL and ATO in combination and found that nontoxic dosage of PTL and ATO co-treatment can synergistically inhibit the in vitro and in vivo proliferation activity of HCC cells through suppressing stemness and self-renewal ability and inducing mitochondria-dependent apoptosis. More importantly, USP7-HUWE1-p53 pathway is involved in PTL enhancing ATO-induced apoptosis of HCC cell lines. Meanwhile, accompanied by induction of apoptosis, PTL and ATO evoke autophagic activity via inhibiting PI3K/Akt/mTOR pathway, and consciously controlling autophagy can improve the anti-HCC efficacy of a combination of PTL and ATO. In short, our conclusion represents a novel promising approach to the treatment of HCC.